Semiotic analysis of visual images in modern Ukrainian social posters - Sosnytskyi, Yurii (Ukrainian Cultural Studies, 2024)
Background. The article examines the role of contemporary Ukrainian social posters as a powerful tool of visual communication that not only shapes national identity but also conveys contemporary social values. In particular, it analyzes how visual strategies, compositional solutions, and the use of archetypes contribute to influencing public consciousness. Special attention is given to exploring posters as a cultural phenomenon that reflects socio-political processes and cultural dynamics in Ukraine through symbols and images. The study emphasizes the significance of social posters as a means of strengthening social cohesion and national spirit.Methods. The research adopts a comprehensive approach that integrates several methodologies. Semiotic analysis was employed to uncover the multilayered meanings of symbols and visual images in social posters, designed to establish an emotional connection with the audience. Content analysis of poster archetypes identified key images that have the most significant impact on viewers. Visual analysis was used to explore the compositional, coloristic, and aesthetic decisions that ensure the effectiveness of posters in audience perception. Each method contributed to revealing the specifics of the visual language of Ukrainian social posters.Results. The findings indicate that contemporary Ukrainian social posters exhibit high aesthetic and communicative effectiveness through the thoughtful integration of visual and semantic elements. Artistic and expressive principles, such as the use of symbolism, typography, and color schemes, enhance the emotional impact of posters. Particular attention is drawn to psychological methods employed to shape public opinion and mobilize viewers. The study also highlights the active use of visual archetypes, such as the "hero," "defender," "mother," "home," and "land," which are integral to national and cultural identity. Persistent stereotypes, rooted in collective perceptions and cultural codes, further amplify communication effectiveness.Conclusions. Based on the conducted analysis, it can be concluded that contemporary Ukrainian social posters are a vital component of cultural discourse, effectively combining emotional and rational influences on the audience. The use of archetypes and symbols ensures a deep emotional connection with viewers, fostering national identity, shaping civic awareness, and stimulating social dynamics. Social posters in Ukraine demonstrate substantial impact through the integration of visual and semiotic elements, making them universal tools of communication and influence.
Keywords: social poster; psychological influence; visual communication; cultural identity; archetypes; national symbols; Ukraine